Is hysterectomy a risk factor for urinary incontinence? - Alexander, Maria C.; Londhe, Vaibhav; Ebenezer, Emily D.; Kekre, Aruna N.; Jeyaseelan, Visalakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hysterectomy is the most common gynecological surgery performed. There are few studies evaluating hysterectomy as a risk factor for urinary incontinence. If hysterectomy is found to be a risk factor for developing urinary incontinence, women undergoing hysterectomy can be well informed prior to the procedure regarding the same. The objective of the present study was to study the prevalence of urinary incontinence in post-menopausal women and its relationship to hysterectomy. To evaluate the association of metabolic syndrome, to urinary incontinence. Methods: This study was a prospective cohort study done in Christian Medical College and Hospital, Vellore, Tamil Nadu between December 2016- December 2017. Postmenopausal women both with natural and surgical menopause, were enrolled into the study after an informed consent. The UDI-6 questionnaire was used to assess urinary incontinence. The categorical variables were presented using frequencies and percentages. The comparison of categorical variables was done using Fisher's exact test. The odds ratio and confidence interval were calculated for the prevalence. P value < 0.05 was considered to be statistically significant. Results: A total of 600 women were enrolled into the study with 300 women having attained natural menopause and 300 women with a surgical menopause. The prevalence of urinary incontinence among these post-menopausal women was 46.24%. The prevalence of urinary incontinence amongst the women with natural menopause was 47.3% and amongst the women with surgical menopause was 45% (p = 0.566). Women with metabolic syndrome suffered from urinary incontinence more than their counterparts without metabolic syndrome (55.8% vs. 36%, p <0.0001). Conclusions: The prevalence of urinary incontinence in the natural menopause and surgical menopause groups was similar, thus proving that hysterectomy is not a risk factor for developing urinary incontinence. However, metabolic syndrome was found to be associated with urinary incontinence.